A GROUNDED THEORY OF EFFECTIVE READING BY PROFOUNDLY DEAF ADULTS. - Silvestri, Julia A.; Wang, Ye (American Annals of the Deaf)
THE PURPOSE of the study was to uncover and describe psycholinguistic and sociocognitive factors facilitating effective reading by signing adults who are profoundly deaf and do not use hearing technology. The sample comprised four groups, each consisting of 15 adults, for a total of 60 participants. The four groups were deaf high- achieving, deaf low-achieving, hearing high- achieving, and hearing low- achieving. Measurements included a language background interview and think- aloud reading discussion. Through the lens of a grounded theory approach, the conditions that facilitate effective reading were uncovered--by coding and categorizing themes, relating the codes and categories, and determining a central theme. It was found that there are similarities and differences in how deaf and hearing people process phonological codes and conceptualize language, and that access to varied instructional strategies and meaningful language experiences is an overarching theme in effective reading.